Buyang Huanwu decoction facilitates neurorehabilitation through an improvement of synaptic plasticity in cerebral ischemic rats - Ruihuan Pan; Jun Cai; Lechang Zhan; Youhua Guo; Run-Yue Huang; Xiong Li; Mingchao Zhou; Dandan Xu; Jie Zhan; Hongxia Chen (BMC, 2017)
Abstract Background Loss of neural function is a critical but unsolved issue after cerebral ischemia insult. Neuronal plasticity and remodeling are crucial for recovery of neural functions after brain injury. Buyang Huanwu decoction, which is a classic formula in traditional Chinese medicine, can positively alter synaptic plasticity. This study assessed the effects of Buyang Huanwu decoction in combination with physical exercise on neuronal plasticity in cerebral ischemic rats. Methods Cerebral ischemic rats were administered Buyang Huanwu decoction and participated in physical exercise after the induction of a permanent middle cerebral artery occlusion. The neurobehavioral functions and infarct volumes were evaluated. The presynaptic (SYN), postsynaptic (GAP-43) and cytoskeletal (MAP-2) proteins in the coronal brain samples were evaluated by immunohistochemistry and western blot analyses. The ultrastructure of the neuronal synaptic junctions in the same region were analyzed using transmission electron microscopy. Results Combination treatment of Buyang Huanwu decoction and physical exercise ameliorated the neurobehavioral deficits (p < 0.05), significantly enhanced the expression levels of SYN, GAP-43 and MAP-2 (p < 0.05), and maintained the synaptic ultrastructure. Conclusions Buyang Huanwu decoction facilitated neurorehabilitation following a cerebral ischemia insult through an improvement in synaptic plasticity. Graphical abstract The Buyang Huanwu decoction (BYHWD) combined with physical exercise (PE) attenuates synaptic disruption and promotes synaptic plasticity following cerebral ischemia (stroke).